Дослідження могильника ХІ—ХІІ ст. у Чернігові - Моця, О.П.; Скороход, В.М.; Жигола, В.С.; Ситий, Ю.М. (Археологія і давня історія України, 2022)
Висвітлюються результати дослідження курганного і ґрунтового могильника ХІ—ХІІ ст. на території Чернігова, характеризується планувальна
структура, розглядаються виявлені археологічні матеріали. The materials of archaeological research in 2020 on
the territory of the mound and moundless necropolises
belonged to the Old Rus Chernihiv are examined and
analyzed in the paper.
This is the area on the border of suburb and the territory
beyond it, where the remains of a barrow necropolis
(11th century) and the moundless burial ground (city cemetery
of the 11th — mid-13th centuries) were discovered.
The barrows which were visible as early as the
18th century, belonged to the first stage of the burial
ground functioning.
A total of 65 moundless burials were discovered.
Judging by individual cases of cutting some graves by
later ones we can confidently talk about the duration
of the existence of the moundless burial ground in this
area. The discovery of the rim of a pot of the 12th century
and fabric from the collar may indicate the burials in
the 12th century as well. Thus, the site was used for at
least 200 years. During this time, the barrow mounds
were significantly leveled, the external signs of moundless
burials of the 11th century disappeared from the
surface but the site continued to be used.
It is noteworthy that burials in the moundless necropolis
are mainly without grave goods which is characteristic
of the Christian tradition. The find of the pendant
with the image of a trident is of great interest. It belongs
to the official two-sided pendants of the end of the
10th — the first half of the 11th century and were used as
the badges of officials of the princely apparatus. Judging
by the features of the images of tridents on the obverse
and reverse, the period of use of the pendant covers the
reigns of Mstislav and Yaroslav Volodymyrovyches.